2013
DOI: 10.1186/1471-2458-13-1171
|View full text |Cite
|
Sign up to set email alerts
|

Rates and risk factors for drug resistance tuberculosis in Northeastern China

Abstract: BackgroundDrug-resistant tuberculosis (TB) has emerged as a major challenge toward TB control and prevention. In Lianyungang city, the extent and trend of drug resistant TB is not well known. The objective of the survey was to assess drug resistance pattern of MTB and risk factors for drug resistant TB, including multidrug resistance tuberculosis (MDR-TB) in this area.MethodsWe performed drug susceptibility testing on Mycobacterium tuberculosis (MTB) isolates with first- and second-line anti-tuberculosis drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
34
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 25 publications
11
34
7
Order By: Relevance
“…Previous TB treatment, a well-known risk factor for drug-resistant TB [7] [9]- [11] [14] [15] was also found to be significantly associated with drug resistance in the present study. Although drug-resistant TB can be transmitted between individuals (primary resistance), most cases arise after inadequate treatment allowing a drug-resistant strain to become dominant [10].…”
Section: Discussionsupporting
confidence: 65%
“…Previous TB treatment, a well-known risk factor for drug-resistant TB [7] [9]- [11] [14] [15] was also found to be significantly associated with drug resistance in the present study. Although drug-resistant TB can be transmitted between individuals (primary resistance), most cases arise after inadequate treatment allowing a drug-resistant strain to become dominant [10].…”
Section: Discussionsupporting
confidence: 65%
“…The studies from Ethiopia reported the proportion of resistance to RIF was in range of 0% -1.9% [15]. Similarly, the higher rate (5.9%) of RIF monoresistance was reported from Northeastern China [25]. In the similar study conducted in Nepal, monoresistance to INH, RIF, EMB and SM was 9.31%, 3.1%, 0.62% and 19.25% respectively [26].…”
Section: Discussionsupporting
confidence: 49%
“…It could be due to poor nutritional status of women because women compromise their own nutrition in order to ensure other family members are adequately nourished. The similar survey conducted at Northeastern China showed females are more likely to suffer from TB than males [25] but another similar study showed male gender was at the higher risk of MDR-TB [30]. Some studies have also reported previous treatment and age group 24 -54 years to be risk factors of MDR-TB [25] [30].…”
Section: Discussionmentioning
confidence: 95%
“…The MDR-TB prevalence rate in previously treated cases is higher than that in new TB cases around the world. In our study area, there are more than six times as many previously treated cases as new cases (19). The PPV usually reaches above 90% in drug resistance diagnostic assays only when the prevalence of resistance is above 15% (18,28).…”
Section: Discussionmentioning
confidence: 99%
“…As a parallel test, p-nitrobenzoic acid (PNB) was utilized for nontuberculous mycobacterium (NTM) identification. Growth in LJ medium containing PNB indicates that the bacilli do not belong to the M. tuberculosis complex (19). For internal quality assurance of DST, a standard H37Rv strain was included with each new batch of LJ medium, and DST was also performed when reading was done after 4 and after 6 weeks.…”
Section: Methodsmentioning
confidence: 99%